Energy differential-based optimal outdoor air ventilation strategy for high-tech cleanrooms concerning free cooling and its performance evaluation. (1st March 2023) - Zhao, Wenxuan; Li, Hangxin; Wang, Shengwei
Abstract: High-tech cleanrooms are essential functional buildings to guarantee normal operation for many high-precision industrial manufacturings. They are usually energy-intensive due to their strict requirements on environmental controls and high space cooling loads generated by manufacturings. Air-side free cooling is a readily available energy-saving measure for buildings by purely inducing adequate outdoor air to neutralize the excessive indoor heat. However, its applications in high-tech cleanrooms are very rare, and no research has discussed "when" and "how much" outdoor air to induce for minimal energy consumption. This study therefore proposes a novel outdoor air ventilation strategy that enables maximum air-side free cooling potential and optimized energy-efficient operation for high-tech cleanrooms under full ranges of weather conditions and application scenarios. This strategy resorts to theoretically formulating "energy differential" (change of cleanroom energy use per unit of outdoor air volume increase) to determine the optimal outdoor air volume. The proposed strategy is tested and validated on three commonly-used air-conditioning systems for high-tech cleanrooms. Results show that annual free cooling hours are 662–2, 537h for the traditional "fully coupled" AHU (air handling unit) system in 31 major Chinese cities. Besides, the energy and economic performance of the proposed strategy are evaluated on eight actual semiconductor clean fabrications with different loads, ventilation requirements, etc. Up to 8% energy saving is achieved in transition months and average 514.2 kWh/m2 electricity and 1.8 GJ/m2 primary energy are saved in a year. Highlights: The air-side free cooling is creatively integrated into high-tech cleanrooms. A novel optimal outdoor air ventilation strategy is proposed accordingly. The strategy is applicable for full ranges of weathers, loads and ventilation rates. The strategy achieves superior performance in transition months by 8% energy saving. Annual average 1.8 GJ/m 2 primary energy is saved for eight actual semiconductor fabs.